Structural model of customer satisfaction using the integration of kansei engineering and kano method - Fevilia Nurnadia, Adria Syaifoel (2014)
This research has been carried out based on the Kansei Engineering (KE) and Kano Method. The Kansei Engineering is used to identify and investigate the customer requirement based on the emotional feeling articulated in Semantic Differential word, while Kano Method (KM) is employed to identify the quality attributes of products based on the functional and dysfunctional attributes. Both approaches are integrated to address what the customer requirements of the products characteristics related to the design elements. All of these processes are combined together as the Structural Model of Customer Satisfaction. The first implication of this study offered a structural models of customer satisfaction in the product development that is not limited to the functionality of products only. The model is a new method in the product development where the perception (KE) and stage of satisfaction (KM) is being taken as one on how to measure the customer satisfaction against the products. Also, this a new model propose the conception on how to develop the product based on Kano requirements and Kansei Engineering . In order to know what the customers perceptions and satisfaction levels of the products, this research involved 220 respondents (college students) in Melaka. Through the questionnaires developed using Kano Method and Kansei Engineering towards the pen products as a case study, the results showed that the final design preference is the design no.4 (grip, clip and click elements). This pen represent the best design selected by respondent since the emotion feeling of comfortable value is 4.63. This design also has the significant correlation to the Kano quality attribute no. 5 (0.303, p<0.01) where the clip element is a highest priority in the design development refers to the structural model. Both of the results in Kano model represent as the 'Indifferent'. This study also found that there is a relationship existed between the KE and KM. The result shows us that the perceived attributes or qualities is impacted or influenced against the emotional design or Kansei responses.